STUDI PERBANDINGAN PENGATURAN CUTI NOTARIS DI INDONESIA DAN BELANDA - Rizqi Perdana Syarif; Mohamad Fajri Mekka Putra (Media Bina Ilmiah, 2025)
A notary, as a public official authorized to create authentic deeds of civil acts, is entitled to legal leave for rest, holidays, medical treatment, or other urgent and legitimate reasons. However, the regulation of notarial leave varies between Indonesia and the Netherlands—the country that introduced the notarial system to Indonesia. Indonesia explicitly regulates notarial leave, while the Netherlands does not, including the BES Islands, which are autonomous territories within the Kingdom of the Netherlands. These regulatory differences give rise to complex legal implications that require thorough examination. This research aims to compare the regulation of notarial leave in Indonesia and the Netherlands, and to analyze the legal consequences of these differences. The study employs a normative juridical method and relies on secondary data sources